An UHPLC-HRMS-Based Untargeted Metabolomics Approach to Explore the Effects of Bacterial Endophyte Co-Culture on Alkanna tinctoria (L.) Tausch Cell Suspension Metabolome - Elodie Bossard; Adrien Cousy; Antonio Grondin; Nikolaos Tsafantakis; Angélique Rat; Nektarios Aligiannis; Anne Willems; Laetitia Cattuzzato; Thien Nguyen; Nikolas Fokialakis (Microorganisms)
Colonization of plant tissues by bacterial endophytes might lead to qualitative and quantitative changes in secondary metabolites (SMs). In this work, in vitro co-culture experiments were performed using cell suspensions of the medicinal plant Alkanna tinctoria and eight of its bacterial endophytes. An untargeted metabolomics approach using Ultra-High-Performance Liquid Chromatography High-Resolution Mass Spectrometry (UHPLC-HRMS) was employed to investigate plant–microbe interactions. Hierarchical clustering analysis and principal component analysis highlighted significant modifications of specific regulation patterns in SM production, caused by bacterial endophytes. The annotation step lead to the identification of 32 stimulated compounds in A. tinctoria cell suspensions. Among them, 3′-hydroxy-14-hydroxyshikonofuran H (5), 8′-decarboxy-rosmarinic acid (18), 8‴-decarboxy-salvianolic B (23), 8″-8‴-didecarboxy-salvianolic acid B (26) were putatively identified for the first time. Our findings highlight that employing selected microbial inoculants under controlled conditions can be an effective strategy for enhancing or stimulating the production of specific high-value metabolites.